Nonlinear Pricing with Reference Dependence - Roseta-Palma, C.; Carvalho, M.; Emanuel-Correia, R. (Oxford Research Encyclopedia of Global Public Health, 2020)
Many utilities, including water, electricity, and gas, use nonlinear pricing schedules which replace a single uniform unit price, with multiple elements such as access charges and consumption blocks with different prices. Whereas consumers are typically assumed to be utility maximizers with nonlinear budget constraints, it is more likely that consumer behavior shows limited-rationality features such as reference dependence. Recent studies of water demand have explored consumer reactions to social comparison nudges, which can moderate consumption and might be a useful tool given low demand-price elasticities. Other authors have noted the difficulties of correct price perception when tariff schedules are complex, and attributed those low elasticities to a lack of information. Nonetheless, it is also possible that consumers form reference prices, relative to which the actual price paid is compared, in a way that affects consumption choices. Faced with a nonlinear price schedule, such as increasing block tariffs, consumers could evaluate their actual marginal price as a loss or a gain relative to a particular reference price that is derived from the schedule. Introducing gain/loss terms into the utility function, in the discrete/continuous model of consumer choice that has been widely used for water demand analysis, leads to consumption decisions that vary when a higher-than-reference price is seen as a loss and a lower-than-reference price as a gain. Utilities might wish to explore these reference-price effects according to their strategic goals. For example, if there are capacity constraints or water scarcity problems, potential water savings can be achieved from highlighting the first-block price as a reference and framing higher-block prices as losses, inducing conservation even without raising overall prices. Furthermore, if higher-block prices are subsequently raised the demand response could be stronger.